Howard Becker: the contemporary of the Chicago school? the theory of labeling in the process of criminalization - Hikal, Wael (2017)
Becker, author who survives to the classics and predecessors of the Chicago’s school, niche of great creators of influential theories in the context of sociology and criminology, by explanations for interaction, learning, exclusion, social structures, among others. This author, comes to realize a synthesis, that seems to be perfected and potentially more accepted and adapted to the present time, with results that often gives the good synthesis, along with the appropriate media, and above all, the argumentation of the experiments and theoretical reviews. Thus, in the present, shows the theory of labeling, along with the processes of qualification of deviant behaviors, who stigmatize them as such and the social effects that cause.